Germanske posuđenice u praslavenskome: pitanja relativne kronologije - Matasović, Ranko (Array, 2000)
It is argued that the majority of Germanic loanwords in Common Slavic underwent certain sound changes that were previously considered Proto-Slavic, e. g. Dybo's law and Illič-Svityč's rule. This has important consequence for the relative chronology of Slavic sound changes.